Financial Distress Zones of Land Transportation Companies Listed on the Indonesia Stock Exchange Using Altman Z-Score - Nurmasari, Ifa; Nur’aidawati, Siti; Harjayanti, Diana Riyana; Macpal, Joshua Husatya (Indonesian Financial Review, 2025)
Passenger land transportation has gained increasing attention in recent years, particularly in relation to corporate financial performance. This study aims to evaluate the financial condition of passenger land transportation sub-sector companies listed on the Indonesia Stock Exchange using the Altman Z-Score method. A descriptive quantitative approach with purposive sampling is employed, resulting in seven selected companies. The study utilizes secondary data obtained from corporate financial statements covering the period from 2019 to 2023. Financial ratios, including working capital, retained earnings, profitability, capital structure, and asset utilization, are analyzed to generate Z-Score values and classify firms into the safe zone, grey zone, and distress zone. The results indicate that four companies fall within the distress zone, one is classified in the grey zone, and two are categorized in the safe zone. These findings highlight varying levels of financial resilience within the passenger land transportation sub-sector.